Motor and Non-motor Symptoms Associated With Exercise Behavior in Parkinson's Disease Patients: Factors Differ Between Patients With and Without Postural Instability - Song, Joomee; Youn, Jinyoung; Huh, Young Eun; Mun, Jun Kyu; Ahn, Jong Hyeon; Lee, Dongyeong; Shin, Woo Young; Cho, Jin Whan (Frontiers in Neurology, 2021)
Background: Exercise is an important treatment for Parkinson’s disease (PD). Therefore, recognizing determinants of exercise behavior for PD based on disease stage is essential. We sought to find whether the determinants differ based on presence of postural instability (PI), which is indicative of disease stage in PD. Methods: We enrolled patients at Samsung Medical Center from September 2019 to November 2020, who had the ability to perform exercise (modified Hoehn and Yahr (HY) stage ≤ 3). All the motor and non-motor symptoms were investigated. The exercise of the PD patients was evaluated using the Physical Activity Scale of the Elderly (PASE)-leisure score. We classified patients into PD without PI (HY stage 1 – 2) and PD with PI (HY stage 2.5 – 3) groups. Multivariate linear regression was performed using backward elimination in each group to determine factors associated with PASE-leisure score. Results: A total of 233 patients were enrolled. In the PD without PI group (n=177), the positive determinant of exercise was Activities-Specific Balance Confidence (ABC) score (β = 0.142, p = 0.032), and the negative determinants were fatigue score (β = −0.228, p = 0.018), female (β = −6.900, p = 0.016) and currently employed status (β = −6.072, p = 0.046). In the PD with PI group (n=56), the positive determinant was non-motor symptom scale (NMSS) score (β = 0.221, p = 0.017) and disease duration (β = 1.001, p = 0.036), while the negative determinants were UPDRS part 3 score (β = −0.974, p < 0.001), UPDRS part 4 score (β = −2.192, p = 0.002), and age (β = −1.052, p < 0.001). Conclusion: Different motor and non-motor symptoms were associated with the exercise in PD patients with and without PI. When encouraging PD patients to exercise, personalized and different strategies should be applied based on the presence of PI.